Effect of oil tankers subdivision on damage stability - ابراهيم باسل; ميشيل بربهان (Latakia University Journal -Engineering Sciences Series, 2024)
This research aims to investigate the impact of oil tankers’ subdivision on damage stability in potential damage scenarios, utilizing the MAXSURF software. The calibration was performed by comparing the mathematical solution outputs with those obtained from the MAXSURF software. Such a calibration was conducted considering the stability of a damaged box-shaped ship using Rhinoceros. The stability of the oil tanker under damaged conditions is then studied. The ship’s hull was designed using Rhinoceros software, and the tank configurations were defined to create two distinct design models.Subsequently, stability analyses were conducted using MAXSURF, considering various assumed damage scenarios. Finally, the results are discussed and the subdivision is evaluated based on the safety levels it achieves when damage occurs. This evaluation was primarily based on hydrostatic calculations and the characteristic values derived from the righting lever curves (GZ).